2014
DOI: 10.1080/09712119.2014.987294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of egg size (weight) and age on hatching performance and chick quality of broiler breeder

Abstract: A total of 2000 Hubbard Classic females and 180 males (male to female ratio 1:11) close to standard body weights were selected and managed separately in the same shed. The objective of this experiment was to study the effects of egg size (small, medium and large) at mid (45 weeks) production cycle and flock age (30, 45 and 60 weeks old) on hatching egg weight loss, fertility, hatchability traits, chick weight and chick yield in a commercial Hubbard Classic broiler breeder flock. The results showed that minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
76
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 43 publications
18
76
1
8
Order By: Relevance
“…This finding is consistent with the data reported by Abudabos et al (2017) for the incubation of eggs of autochthonous free-range chickens, and those by Duman and (2017) for the egg incubation of meattype hybrid. On the contrary, Rosa et al (2002) found a significantly higher total mortality in the group of large eggs of an average weight of 73.2 g (9.6%), compared to eggs of an average weight of 60.0 g (7.0%) and 65.1 g (6 , 7%), which is consistent with the results obtained by Iqbal et al (2016) Kopecký (2015) found the highest total mortality in the group of eggs weighing 70-75 g (16.7%), and the lowest in the group weighing 55-60 g (9.7%). Early embryonal mortality in our study was most pronounced in group XL (18.1%), and lowest in group S (10.8%), with no statistically significant differences , p> 0.05).…”
supporting
confidence: 81%
See 3 more Smart Citations
“…This finding is consistent with the data reported by Abudabos et al (2017) for the incubation of eggs of autochthonous free-range chickens, and those by Duman and (2017) for the egg incubation of meattype hybrid. On the contrary, Rosa et al (2002) found a significantly higher total mortality in the group of large eggs of an average weight of 73.2 g (9.6%), compared to eggs of an average weight of 60.0 g (7.0%) and 65.1 g (6 , 7%), which is consistent with the results obtained by Iqbal et al (2016) Kopecký (2015) found the highest total mortality in the group of eggs weighing 70-75 g (16.7%), and the lowest in the group weighing 55-60 g (9.7%). Early embryonal mortality in our study was most pronounced in group XL (18.1%), and lowest in group S (10.8%), with no statistically significant differences , p> 0.05).…”
supporting
confidence: 81%
“…(2015) determined the absence of statistically significant differences between eggs of different masses for the mid and late mortality. Iqbal et al (2016) found significantly higher early, mid and late mortality in the group of large eggs of an average weight of 70.03 g (3.3, 2.3 and 3.00%, respectively) in relation to the group of eggs of an average weight of 60.05 g (2.0; 1.3 and 1.67%, respectively). The largest mass group (XL) in our study had higher values of early and late mortality, although there was no statistically significant difference, which is in accordance with the results of several authors.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…It is a significant parameter for optimum flock performance . Effects of egg weight on pullet performance have been widely studied (Witt de & Schwalbach, 2004;Alkan et al, 2008;Jiang & Yang 2007;Ulmer-Franco et al, 2010;Egbeyale et al, 2011;Iqbal et al, 2016). However, such studies do not gather growth, carcass parameters, internal organ weights, blood parameters, asymmetry and tonic immobility in a single study.…”
Section: Introductionmentioning
confidence: 99%